The Utilization of a Commercial Soil Nucleic Acid Extraction Kit and PCR for the Detection of Clostridium tetanus and Clostridium chauvoei on Farms after Flooding in Taiwan - HUANG, Shr-Wei; CHAN, Jacky Peng-Wen; SHIA, Wei-Yau; SHYU, Chin-Lin; TUNG, Kwon-Chung; WANG, Chi-Young (Journal of Veterinary Medical Science, 2013)
Clostridial diseases are zoonoses and are classified as soil-borne diseases. Clostridium chauvoei and Clostridium tetani cause blackleg disease and tetanus, respectively. Since bacteria and spores are re-distributed by floods and then, subsequently, contaminate soils, pastures and water; the case numbers associated with clostridial diseases usually increase after floods. Because Taiwan is often affected by flood damage during the typhoon season, possible threats from these diseases are present. Thus, this study’s aim is to apply a combination of a commercial nucleic acid extraction kit and PCR to assess the prevalence of Clostridia spp. in soil and to compare the positivity rates for farms before and after floods. The minimum amounts of Clostridium tetanus and Clostridium chauvoei that could be extracted from soils and detected by PCR were 10 and 50 colony forming units (cfu), respectively. In total, 76 samples were collected from the central and southern regions of Taiwan, which are the areas that are most frequently damaged by typhoons. Noteworthy, the positive rates for Clostridium tetanus and Clostridium chauvoei in Pingtung county after the severe floods caused by a typhoon increased significantly from 13.73 and 7.84% to 53.85 and 50.00%, respectively. This study for the first time provides the evidence from surveillance data that there are changes in the environmental distribution of Clostridium spp. after floods. This study indicates that screening for soil-related zoonotic pathogens is a potential strategy that may help to control these diseases.